An overview of human migrations - Jobling, Mark (Henry Stewart Talks, 2015)
The human genome and human genetic variation, The distribution of genetic diversity, Migration out of Africa, Interbreeding with archaic humans, Examples of genetic adaptation, Later expansions and migrations, The importance of interdisciplinary research